2019
DOI: 10.1021/acsomega.9b00135
|View full text |Cite
|
Sign up to set email alerts
|

Silicoaluminophosphate (SAPO)-Templated Activated Carbons

Abstract: Microporous activated carbon was prepared by depositing and pyrolyzing propylene within the microporous voids of SAPO-37 and subsequently removing the template by a treatment with HCl and NaOH. The carbon had a high surface area and large micropore and ultramicropore volumes. The yield, crystallinity, morphology, and adsorption properties compared well with those of a structurally related zeolite-Y-templated carbon. No HF was needed to remove the SAPO-37 template in contrast to the zeolite Y template, which co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Here, we should note, that the loss of the zeolite templates is the fundamental disadvantage of the proposed process. There are several potential solutions to this problem, including, using cheaper templates [43], waste zeolite materials (i.e. spent FCC catalysts [44] or zeolite materials produced from industrial waste [45]), and even recycling of the zeolite template.…”
Section: High-quality Ztc Materials From Fe/bea and Fe/fau Templatesmentioning
confidence: 99%
“…Here, we should note, that the loss of the zeolite templates is the fundamental disadvantage of the proposed process. There are several potential solutions to this problem, including, using cheaper templates [43], waste zeolite materials (i.e. spent FCC catalysts [44] or zeolite materials produced from industrial waste [45]), and even recycling of the zeolite template.…”
Section: High-quality Ztc Materials From Fe/bea and Fe/fau Templatesmentioning
confidence: 99%
“…Hedin and co-workers found that template removal could be achieved with a combination of HCl and NaOH for a silicoaluminophosphate-templated carbon, however this is likely due to less chemical robustness compared to a pure aluminosilicate framework. 207 NaOH has been shown to be at least partially effective in desilicating zeolites, so does show some promise for removal of actual zeolite templates from ZTCs, 208 and has been attempted on a few occasions. 176,[209][210][211] Moon et al found that washing with hot NaOH followed by HCl resulted in complete removal of Al, but left residual Si in the resultant ZTCs.…”
Section: Materials Advancesmentioning
confidence: 99%
“…SAPO-37 molecular sieve shares the FAU topology like the industrially widely used Y zeolite . With a three-dimensional 12-membered ring pore structure (12-MR, formed by the ordered connection of SOD cages through the double 6-membered ring) and large supercages, this microporous material has attracted the attention of researchers since its discovery. Unlike Y zeolite, the framework of SAPO-37 primarily consists of P and Al atoms, with Si partially substituting some P atoms through the SM2 mechanism . This results in the majority of Si existing in the form of Si­(4Al) in SAPO-37, leading to a significant number of Brønsted acid sites. , The acidity of SAPO-37 is notably milder compared to Y zeolite, making it advantageous in weak acid catalysis applications. , For example, in the liquid-phase Beckmann rearrangement reaction of cyclohexanone oxime, SAPO-37 demonstrated superior activity and selectivity when compared to traditional ZSM-5 and Y zeolites .…”
Section: Introductionmentioning
confidence: 99%